Performance analysis of IRS‐aided cooperative NOMA‐MEC system - Xuehua Li; Ziwei Liu; Xiequn Dong; Xinwei Yue; Wanwei Tang (IET Communications, 2022)
Abstract In this paper, an intelligent reflecting surface (IRS) assisted cooperative non‐orthogonal multiple access and mobile edge computing (NOMA‐MEC) system is proposed, where a base station sends signals to users through the virtue of the IRS. When the direct links between the base station and the user are blocked, the offloading tasks will be refracted to the near‐end user through the IRS and forwarded to the remote user, where the near‐end user is equipped with an MEC server working at full duplex or half duplex mode. To evaluate the potential performance of IRS aided cooperative NOMA‐MEC, new closed‐form expressions of the offloading outage probability is deduced for a pair of users. The asymptotic expressions of offloading outage probability are provided in the high signal‐to‐noise ratio regime. Simulation results are presented to substantiate the analyses and demonstrate that: (i) The offloading outage behaviors of IRS‐aided cooperative NOMA‐MEC systems are superior to that of NOMA‐MEC without IRS and IRS‐aided OMA‐MEC; (ii) As the value of parameter Q increases, the IRS‐aided NOMA‐MEC system is capable of achieving the enhanced offloading outage performance; (iii) By comparing with NOMA‐MEC without IRS and IRS‐aided OMA‐MEC, the energy efficiency and system throughput of IRS‐aided NOMA‐MEC has obvious advantages in delay‐limited transmission mode.